2021
DOI: 10.1021/acsabm.1c00745
|View full text |Cite
|
Sign up to set email alerts
|

Concise Nanoplatform of Phycocyanin Nanoparticle Loaded with Docetaxel for Synergetic Chemo-sonodynamic Antitumor Therapy

Abstract: Combined chemotherapy and sonodynamic therapy (chemo-SDT) based on the nanoplatform/nanocarrier is a potential antitumor strategy that has shown higher therapeutic efficacy than any monotherapy. Therefore, a safe and effective multifunctional system with a concise design and simple preparation process is urgently needed. In this work, by using a one-step cross-linking method, a multifunctional nanosystem, which employs phycocyanin nanoparticles (PCNPs) as a nanocarrier to deliver the chemotherapy drug docetaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The DLS analysis demonstrated a normal distribution of particle sizes, with an average diameter of 175.2 nm, while the TEM image con rmed a consistent spherical shape of the PCNP. These ndings align with previous studies that reported successful synthesis of phycocyanin nanoparticles with similar characteristics (Huang et al 2017;Cao et al 2021). However, it is important to note that the measurements obtained by DLS and TEM may differ due to the different principles underlying each method.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The DLS analysis demonstrated a normal distribution of particle sizes, with an average diameter of 175.2 nm, while the TEM image con rmed a consistent spherical shape of the PCNP. These ndings align with previous studies that reported successful synthesis of phycocyanin nanoparticles with similar characteristics (Huang et al 2017;Cao et al 2021). However, it is important to note that the measurements obtained by DLS and TEM may differ due to the different principles underlying each method.…”
Section: Discussionsupporting
confidence: 92%
“…PC has been found to have potent antioxidant and anti-in ammatory properties, as well as protection against UVB-induced apoptosis. Its ability to absorb light makes it a potential candidate for sunscreens, while its low toxicity pro le makes it safe for cosmetics (Cao et al 2016;Cao et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 41 Moreover, an increase in the speed and accumulation of drug release was found in the ultrasound treatment groups, indicating that ultrasound exposure could aggravate PLGA structural destruction and degradation, consistent with the literature reports and our research results. 8 , 42 , 43 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, SDT was found to promote cancer cells’ drug sensitivity by improving cellular internalization of chemotherapeutic drugs, activating the mitochondria-caspase signaling pathway, and down-regulating the expression of ATP-binding cassette transporters ( Ding et al, 2017 ; Xu et al, 2020a ; Ren et al, 2022 ). These functions enhanced the cytotoxicity of chemotherapeutic factors and therefore contributed to the promoted therapeutic efficiency ( An et al, 2020a ; Zhang et al, 2021b ; Cao et al, 2021 ; Zhang et al, 2021c ).…”
Section: Sonodynamic Therapymentioning
confidence: 99%